The relationship between cognitive function and cortical thickness in first-episode drug-naive schizophrenia patients with agitation - Liang, Qian; Li, Yan; Zhou, Chao; Zhang, Rongrong; Lu, Shuiping; Shen, Xuran; Jiang, Fuli; Xie, Shiping (Frontiers in Psychiatry, 2025)
ObjectiveThis study aims to explore the relationships between the agitation behavior, cognitive function and cortical thickness in first-episode drug-naïve schizophrenia (FESN).MethodsA total of 55 male healthy controls (HC) and 79 male inpatients with FESN were enrolled in the present study. Whole brain cortical thickness was extracted from T1-weighted MRI using Freesurfer Version 7.4.1 software package. Cognitive function was evaluated using the MATRICS Consensus Cognitive Battery (MCCB). The Positive and Negative Syndrome Scale-Excited Component (PANSS-EC) is used to divide these inpatients into agitation group (FESN+A) and non-agitation group (FESN+NA). Correlation analysis was employed to investigate the potential associations between cortical thickness and cognitive function.ResultsThe FESN+A group had higher Positive and Negative Syndrome Scale (PANSS) total score, positive symptom score, and general psychopathology score than the FESN+NA group. Both the FESN+A/NA groups showed significantly worse performance than the HC in symbol coding, working memory, attention/vigilance, reasoning and problem solving, and social cognition. The FESN+A group performed worse on working memory when comparing to FESN+NA group. Furthermore, the cortical thickness of the left paracalcarine gyrus was increased in the FESN+NA group, compared to HC. FESN+A group had thicker cortical thickness in the right posterior cingulate cortex (rPCC) compared with the FESN+NA group. The cortical thickness of rPCC was negatively correlated with score of working memory in the FESN+A group.ConclusionThe present study demonstrated that the abnormal cortical thickness of rPCC may be related to the agitation behavior and cognitive function in patients with FESN+A, suggesting a potential treatment target for agitation behavior and cognitive impairment in schizophrenia.